Análise crítica do plano de gerenciamento de resíduos sólidos perigosos (Classe I) de uma indústria farmacêutica - Martins, Raissa Cristina Faria [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
O presente trabalho realizou uma análise crítica do Plano de Gerenciamento de Resíduos (PGR) dos resíduos sólidos perigosos (Classe I) de uma indústria farmacêutica. Nesta, foram mapeados os resíduos gerados e suas fontes geradoras, em seguida foi realizada a segregação desses resíduos em Classe I e Classe II. Foram posteriormente estudadas as destinações aplicadas para cada tipo de resíduo perigoso e se o Plano de Gerenciamento de Resíduos está em conformidade com a Política Nacional de Resíduos Sólidos (PNRS), com a Resolução de Diretoria Colegiada RDC nº222 e com a norma ISO 14001, em seguida foram levantadas oportunidades de melhoria na destinação dos resíduos. Ao final da análise verificou-se que o PGR desenvolvido pela empresa está em consonância com as legislações estudadas e atende os requisitos da norma ISO 14001, possui apenas 2 oportunidades de melhoria em relação a destinação final ambientalmente mais adequada de acordo com a Política Nacional de Resíduos Sólidos. Constatou-se que o resíduo que apresenta maior representatividade dentre os resíduos gerados é o Sólido Perigoso, com cerca de 86% do volume total gerado que já é destinado ao coprocessamento, sendo uma boa destinação ambiental ao que se refere a prioridade estabelecida pela PNRS.

The present work carried out a critical analysis of the Waste Management Plan (WMP) of hazardous solid waste (Class I) from a pharmaceutical industry. In this, the generated waste and its generating sources were mapped, then the segregation of these wastes into Class I and Class II was carried out. Subsequently, the destinations applied for each type of hazardous waste were studied and whether the Waste Management Plan complies with the National Solid Waste Policy (PNRS), with the Resolution of the Collegiate Board of Directors RDC nº222 and with the ISO 14001 standard, in Opportunities for improvement in waste disposal were then raised. At the end of the analysis, it was found that the PGR developed by the company is in line with the legislation studied and meets the requirements of the ISO 14001 standard, it has only 2 opportunities for improvement in relation to the most environmentally appropriate destination in accordance with the National Policy on Solid Waste. It was found that the residue that has the greatest representation among the generated waste is the Hazardous Solid, with about 86% of the total volume generated that is already destined for co-processing, being a good environmental destination with regard to the priority established by the PNRS.
Critical analysis of the solid waste management plan hazardous substances (Class I) of a pharmaceutical industry
Keywords: Resíduos sólidos; Gestão Ambiental; Indústria Farmacêutica; Waste management plan; Solid waste; Pharmaceutical Industry